2015
DOI: 10.1128/mbio.01168-15
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Genome Sequence of Clostridium aceticum: a Missing Link between Rnf- and Cytochrome-Containing Autotrophic Acetogens

Abstract: Clostridium aceticum was the first isolated autotrophic acetogen, converting CO2 plus H2 or syngas to acetate. Its genome has now been completely sequenced and consists of a 4.2-Mbp chromosome and a small circular plasmid of 5.7 kbp. Sequence analysis revealed major differences from other autotrophic acetogens. C. aceticum contains an Rnf complex for energy conservation (via pumping protons or sodium ions). Such systems have also been found in C. ljungdahlii and Acetobacterium woodii. However, C. aceticum also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 55 publications
(62 reference statements)
2
62
0
Order By: Relevance
“…DSM 2634=ATCC 13726). Subsequent analyses of 16S rRNA gene sequences showed that members of three proposed genera (listed as genera 6, 7 and 8 in Collins et al , 1994), namely ‘ C. aminobutyricum’ , Clostridium felsineum , Clostridium formicaceticum , and Clostridium halophilum , along with the more recently described Clostridium caminithermale , form a relatively compact separate group that also includes Clostridium aceticum and Anaerovirgula multivorans (Brisbarre et al , 2003; Chen et al , 2006; Pikuta et al , 2006; Gerritsen et al , 2014; Poehlein et al , 2015; Lawson et al , 2016). In the 2009 edition of Bergey’s, these species were assigned to Clostridiaceae 2, a sister group to Peptostreptococcaceae (Ludwig et al , 2009b), and are listed the same way in the SILVA database (Yilmaz et al , 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DSM 2634=ATCC 13726). Subsequent analyses of 16S rRNA gene sequences showed that members of three proposed genera (listed as genera 6, 7 and 8 in Collins et al , 1994), namely ‘ C. aminobutyricum’ , Clostridium felsineum , Clostridium formicaceticum , and Clostridium halophilum , along with the more recently described Clostridium caminithermale , form a relatively compact separate group that also includes Clostridium aceticum and Anaerovirgula multivorans (Brisbarre et al , 2003; Chen et al , 2006; Pikuta et al , 2006; Gerritsen et al , 2014; Poehlein et al , 2015; Lawson et al , 2016). In the 2009 edition of Bergey’s, these species were assigned to Clostridiaceae 2, a sister group to Peptostreptococcaceae (Ludwig et al , 2009b), and are listed the same way in the SILVA database (Yilmaz et al , 2014).…”
mentioning
confidence: 99%
“…Also, aside from the genome of C. aceticum (Poehlein et al , 2015), there was almost no sequence data to verify the 16S rRNA gene-based tree. Therefore, these organisms were excluded from further analysis.…”
mentioning
confidence: 99%
“…The cluster of genes encoding enzymes of the methyl and carbonyl branches of the Wood-Ljungdahl pathway is present in the genome and showed the same organization as described for S. ovata DSM 2662 (6). The genome contains genes encoding for enzymes involved in the metabolism of one-carbon compounds, including cooS for the putative synthesis of the carbon monoxide dehydrogenase (CODH) required for growing on CO. Five genes of the formate dehydrogenase ( fdhs ) complex involved in the oxidation of formate were also detected.…”
Section: Genome Announcementmentioning
confidence: 76%
“…Genes encoding enzymes of the methyl and carbonyl branches of the Wood-Ljungdahl pathway are conserved within acetogenic bacteria (11). Correspondingly, the genome of B. methylotrophicum harbors a gene cluster that is highly similar to the respective cluster of E. limosum ATCC 8486 T and harbors genes encoding the Rnf complex.…”
Section: Genome Announcementmentioning
confidence: 99%